The Influence of Service Quality, Sales Promotion, and Social Capital on Service Switching Behavior in Building Material Retail in Greater Malang: A Push–Pull–Mooring (PPM) Perspective - Yusisca Yofa Yulanda; Sri Palupi Prabandari; Radityo Putro Handrito (Global Research Collaboration, 2026)
This study aims to examine the effects of service quality and sales promotion on service switching behavior, as well as the moderating role of social capital among customers of traditional building material stores in Greater Malang, Indonesia. A quantitative explanatory research design was employed using a cross-sectional survey of 250 customers selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both the measurement and structural models. The results indicate that service quality has a significant negative effect on service switching behavior, while sales promotion has a significant positive effect. Social capital significantly moderates the relationship between service quality and service switching behavior but does not moderate the relationship between sales promotion and service switching behavior. The structural model explains 28.8% of the variance in service switching behavior. The findings confirm the applicability of the Push–Pull–Mooring framework in explaining customers' switching behavior in traditional building material stores. Strengthening service quality and fostering social capital are important strategies for reducing customers' switching intentions and enhancing long-term competitiveness.